Nowe zadania controllingu strategicznego - Fjałkowska, Danuta (New tasks of strategic controllership, 2006)
This paper is an attempt to outline broad and multi-faceted problems of a new role of strategic controllership as a mechanism capable of generating its own conceptual managerial solutions. These solutions are based on simultaneous implementation the acknowledged management concepts and/or their elements integrated and coordinated in a new dynamic value. The elements should be appropriate on a timely basis and individual for each organisation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 112-120